Peran Pemerintahan Desa Dalam Pemberdayaan Pengerajinan Purun di Desa Mekar Jaya Kecamatan Wampu Kabupayen Langkat - Suyono, Suyono; Adam , Adam; Kusmanto, Heri (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
This study aims to analyze the role of the village government in empowering purun artisan businesses in Mekar Jaya Village, Wampu District, Lalat Regency. The method used is qualitative descriptive with data collection techniques through in-depth interviews, participatory observation, and documentation. The research informants include village heads, community empowerment officers, and purun artisans. The study results show that the village government's role in empowering purun artisans in Mekar Jaya Village is very strategic, including the role of regulator, dynamizer, facilitator, and catalyst. The village government runs various programs such as skills training, marketing facilitation, network development, and supervision and evaluation of empowerment programs, which positively impact the capacity, productivity, and welfare of artisans. However, empowerment efforts still face challenges such as limited access to capital, low quality of human resources, limited marketing, inadequate infrastructure, fierce market competition, and lack of private sector support. Therefore, an integrated and collaborative sustainable strategy is needed to increase program effectiveness, expand access to technology and markets, and strengthen partnerships with various parties to support village economic growth and community welfare.